Mycophenolate Mofetil induces c-Jun-N-terminal kinase expression in 22Rv1 cells: an impact on androgen receptor signaling - Zenata, Ondrej; Dvorak, Zdenek; Vrzal, Radim (Journal of Cancer, 2018)
Mycophenolate Mofetil (MYC) is a transplant drug used to prevent rejection in heart and kidneys transplant patients. Inosine monophosphate dehydrogenase (IMPDH), an enzyme involved in de novo synthesis of guanosine nucleotides, was considered as a primary target for MYC. Recently, we described that MYC was activates aryl hydrocarbon receptor and it antagonizes glucocorticoid receptor. Here we describe an androgen receptor (AR) as another off-target for MYC. We found that MYC increased basal and dihydrotestosterone (DHT)-inducible AR-dependent luciferase activity in AIZ-AR cells. In the same manner it induced or augmented mRNA level of KLK3 (prostate specific antigen; PSA) in 22Rv1 cells. Herein it displayed a hormetic effect on proliferation activity, since it significantly stimulated proliferation in lower concentrations but inhibited in higher (>1 µg/ml) concentrations in the presence of DHT. In contrast, MYC suppressed DHT-inducible KLK3 mRNA expression and cell proliferation in androgen-dependent LNCaP cells. MYC augmented DHT-inducible nuclear translocation of AR and increased the expression of MAPK8/9 (JNK46/54) resulting in the drop of their phosphorylation status. Moreover, MYC sensitized DHT-treated 22Rv1 cells to JNK-IN-8 mediated growth inhibition with the drop of IC50 from 1425 nM to 84 nM within 24 hrs. In conclusion, we suggest that, castrate-resistant prostate cancers progression might be retarded with the combination of MYC and chemical JNK inhibitors, involving AR-dependent mechanism.
Keywords: JNK; LNCaP; proliferation; 22Rv1; Mycophenolate